ПРЕЗИДЕНТ ШАВКАТ МИРЗИЁЕВ – МИЛЛЕТЛЕРАРА ҲӘМ ДИНЛЕРАРА ТАТЫЎЛЫҚ ҲАҚҚЫНДА - Абаев, С.; Якубов, М.; Сарыбаев, М. (SCIENCE and SOCIETY, 2024)
The article deals with the notion of ideas international agreement and religious tolerance on the basis of works of President Sh.Mirziyoyev.
Keywords: New Uzbekistan; strategy; Renaissance; congregation; international agreement; friendship; theology; radicalize; national center; international; concord; charity